Response of Macrobrachium rosenbergii to Vegetable Oils Replacing Dietary Fish Oil: Insights From Antioxidant Defense - Sun, Cunxin; Liu, Bo; Zhou, Qunlan; Xiong, Zhe; Shan, Fan; Zhang, Huimin (Frontiers in Physiology, 2020)
The study was conducted to evaluate the effects of fish oil replacement by vegetable oils on growth performance, histology, antioxidant capacity of Macrobrachium rosenbergii. Three isonitrogenous and isoenergetic diets were formulated with different lipid sources included. DFO diet contained 6% fish oil, whereas DSO and DRO diets included 6% soybean oil and rapeseeds oil as alternatives for fish oil, respectively. Prawns were fed thrice daily for 8 weeks. The results showed that prawns in DFO group showed significantly lower final weight, weight gain ratio and specific growth rate, but higher feed intake and feed coefficient ratio than those in DSO and DRO group. DFO group also showed distorted and atrophic visible and apoptosis in ultrastructure of hepatocytes compared with other groups. In addition, levels of haemolymph proinflammatory cytokines, activities of anti-superoxide anion, inducible-type NO-synthase and content of nitric oxide, and hepatopancreas NF-κB signal pathway gene expression in DFO group increased markedly than those of DSO and DRO groups. The results suggested that vegetable oils, such as soybean oil and rapeseeds oil might be the better lipid sources in diets for Macrobrachium rosenbergii than fish oil, it may be attributed to modified oxidative status induced by NF-κB-NO signal pathway.